KONTRIBUSI MOTIVASI INTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP N 1 SAMBI TAHUN AJARAN 2015/ 2016 - Widi Nuriski, Atika, Idris Harta, M.A., Ph.D (2015)
The purpose of this study is (1) to analyze and examine the contribution of intrinsic motivation to mathematics learning outcomes, (2) to analyze and examine the contribution of extrinsic motivation to mathematics learning outcomes, (3) to analyze and examine the contribution of intrinsic motivation and extrinsic motivation to mathematics learning outcomes. This research is a quantitative-correlative, because the data used in the form of numbers and explain the relationship between the variables.. This study took place in SMPN 1 Sambi Boyolali with a sample of 55 students of class VII. The methods of data collected by questionnaires and documentation. Data were analyzed using multiple regression analysis. The results showed that: the motivation of the intrinsic provide a positive and significant effect on learning mathematics outcomes, the motivation of the extrinsic provide a positive and significant effect on learning mathematics outcomes, jointly intrinsic motivation and extrinsic motivation to learn a positive influence and significant the results of learning math.